In Vitro Reactivity of the Glucose Degradation Product 3,4-Dideoxyglucosone-3-ene (3,4-DGE) towards Abundant Components of the Human Blood Circulatory System - Auditore, Andrea; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika (International Journal of Molecular Sciences, 2022)
3,4-Dideoxyglucosone-3-ene (3,4-DGE) is a glucose degradation product present in processed foods and medicinal products. Additionally, its constant formation from 3-deoxyglucosone in plasma has been suggested. Due to its α,β-unsaturated dicarbonyl moiety, 3,4-DGE is highly reactive and has shown harmful effects in vitro. Here, we investigated the impact of major components of the human blood circulatory system on 3,4-DGE in vitro. Under physiological conditions, plasma concentrations of human serum albumin (HSA) reacted efficiently with 3,4-DGE, resulting in only 8.5% of the initial 3,4-DGE concentration after seven hours (vs. 83.4% without HSA, p < 0.001). Thereby, accessible thiol groups were reduced from 0.121 to 0.064 mol/mol HSA, whereas ketoprofen binding and esterase-like activity of HSA were not affected. Plasma concentrations of glutathione (GSH) reacted immediately and completely with 3,4-DGE, leading to two stereoisomeric adducts. Plasma concentrations of immunoglobulin G (IgG) bound to 3,4-DGE to a lower extent, resulting in 62.6% 3,4-DGE after seven hours (vs. 82.2% in the control, p < 0.01). Immobilized human collagen type IV did not alter 3,4-DGE concentrations. The results indicated that particularly HSA, GSH, and IgG readily scavenge 3,4-DGE after its appearance in the blood stream, which may be associated with a reduced antioxidative and cytoprotective activity for the living cells and, thus, the human organism by blocking free thiol groups.
CRIS-Team Scopus Importer:2022-04-29
Keywords: 3; 4-dideoxyglucosone-3-ene (3; 4-DGE); collagen type IV; diabetes; glucose degradation product; glycation; human serum albumin; immunoglobulin G; L-glutathione; oxidative stress; α; β-unsaturated dicarbonyl